Study guides

☆☆

Q: Is m plus n equals n plus m commutative?

Write your answer...

Submit

Still have questions?

Related questions

no

Commutative

The value of n is 3, by the commutative property.

m = n/(n-1)

no

m + n = 10000.05m + 0.06n = 57

87

It would be the same number either way because its addition.

N=l-m

If: m = n+x/p then x = p(m-n)

Yes. Matrix addition is commutative.

m = 24

12/n+7m=30 12/6=2 + 7x4=28

This is a hyperbola. It is best approached using Fermat's factorisation method. Seefermat-s-factorization-methodor google wikepedia. I don't know of any faster approach.

you multiply m n p

We have no clue what question that equation is asking.

n = 8

Solve be substitution... m+n=1000 0.05m+0.06n=57 Take one of the equation and find "m" m=1000-n substitute into the other equation 0.05(1000-n)+0.06n=57 50-0.05n+0.06n=57 50-0.01n=57 -0.01n=-7 n=700 Now you have found "n" now find "m" m=1000-n m=1000-700 m=300 m=300 and n=700

Given m equals 3 and n equals 1 then m3n3 equals?m3n3 = m*3*n*3 = 3*3*1*3 = [ 27 ]

2 plus n is the true one, but 1 plus n is not?

When M equals 25, then M divided by 5 is 5. It makes no difference what N is.

It cannot be proven because it is not true. Suppose S1 = {0,1,2,3} and S2 = {0,5,10} then S1 u S2 = {0,1,2,3,5,10} then |S1| = n = 4, |S2| = m = 3 but |S1 u S2| = 6 which is NOT n+m = 7

y = x2 + 2mx + n complete the square y + m2 = x2 + 2mx + m2 + n = (x + m)2 + n (x + m)2 = y + m2 - n x + m = √(y + m2 - n) x = -m + √(y + m2 - n)

N=0

The Law of 4 Laws of addition and multiplication Commutative laws of addition and multiplication. Associative laws of addition and multiplication. Distributive law of multiplication over addition. Commutative law of addition: m + n = n + m . A sum isn't changed at rearrangement of its addends. Commutative law of multiplication: m · n = n · m . A product isn't changed at rearrangement of its factors. Associative law of addition: ( m + n ) + k = m + ( n + k ) = m + n + k . A sum doesn't depend on grouping of its addends. Associative law of multiplication: ( m · n ) · k = m · ( n · k ) = m · n · k . A product doesn't depend on grouping of its factors. Distributive law of multiplication over addition: ( m + n ) · k = m · k + n · k . This law expands the rules of operations with brackets (see the previous section).